myTunes: Digital music library users and their self-images - Hargreaves, David; Krause, Amanda (Sage Publications Ltd., 2012)
This investigation explored the relationships between individuals’ self-images and their interactions with their digital music collections via the commercially predominant program iTunes. Sixty-nine university students completed an internet-based Musical Self-Images Questionnaire (MSIQ) along with a series of questions concerning their iTunes collections. The majority of participants were highly engaged with music, regardless of their varied musical backgrounds. Factor analysis of the MSIQ data revealed two distinct self-image groups, which we label as ‘musical practitioner’ (linking ‘overall musician’, ‘performer’, ‘composer’, ‘teacher’, and ‘listener’) and ‘music consumer’ (linking ‘listener’, ‘fan’, and ‘technology user’). Participants used an average of seven attributes to categorize their music, and most consistently used one in particular to sort their collections. Those who rated themselves as higher level performers and fans used the playlist function (which involves compiling sequences of selected tracks) more often than those with lower self-ratings on those scales.